Resting Heart Rate Variability, Facets of Rumination and Trait Anxiety: Implications for the Perseverative Cognition Hypothesis - Williams, DeWayne P.; Feeling, Nicole R.; Hill, LaBarron K.; Spangler, Derek P.; Koenig, Julian; Thayer, Julian F. (Frontiers in Human Neuroscience, 2017)
The perseverative cognition hypothesis (PCH) posits that perseveration, defined as the repetitive or sustained activation of cognitive representations of a real or imagined stressor, is a primary mechanism linking psychological (or stress) vulnerability with poor health and disease. Resting vagally mediated heart rate variability (vmHRV) is an important indicator of self-regulatory abilities, stress vulnerability, and overall health. Those with lower resting vmHRV are more vulnerable to stress, and thus more likely to engage in perseverative cognition and experience subsequent negative mental health outcomes such as anxiety. Recent research suggests that rumination – one of the core mechanisms underlying perseveration– is a construct containing (at least) two maladaptive (depressive and brooding) and one adaptive (reflective) types of rumination. However, to date, research has not examined how the association between resting vmHRV may differ between these three facets of rumination, in addition to these facets’ mechanistic role in linking lower resting vmHRV with greater trait anxiety. The current cross-sectional study explores these relationships in a sample of 203 participants (112 females, 76 ethnic minorities, mean age = 19.43, standard deviation = 1.87). Resting vmHRV was assessed during a 5-minute-resting period using an electrocardiogram. Both trait rumination (including the three facets) and anxiety were assessed via self-report scales. Significant negative associations were found between resting vmHRV and maladaptive, but not adaptive, forms of perseveration. Similarly, mediation analyses showed a significant indirect relationship between resting vmHRV and anxiety through maladaptive, but not adaptive, facets of rumination. Our findings support the PCH such that those with stress vulnerability, as indexed by lower resting vmHRV, are more likely to engage in maladaptive perseverative cognition and thus experience negative outcomes such as anxiety. Our data also lend a novel outlook on the PCH; resting vmHRV is not related to reflective rumination and thus, this facet of perseveration may be a neutral, but not beneficial, factor in the link between stress vulnerability and psychological well-being.